Research on cosmetic marketing from the perspective of social media: Based on the difference analysis of emerging brands and luxury brands in China - Wang Yimeng (SHS Web of Conferences)
In contemporary society the social media is very popular, many brands in China choose to promote their products through social media, such as Tik Tok, Xiaohongshu and Weibo. Nowadays, some luxury brands have also invested in the promotion of social media. So, what are the similarities and differences between some local brands in China that have sprung up and appeared in recent years? This paper will analyze their effects and benefits through their differences in promotion. Luxury brands this article wants to analyze: Estee Lauder, emerging brand this article wants to analyze: Perfect Diary. This paper will analyze the marketing strategies, marketing differences, marketing trends and marketing deficiencies of emerging brands and luxury brands respectively. In the process of analysis, this study will use comparative investigation, case study and case analysis. It is true that different brands have different strategies for promotion. In the social media era, there are many different promotion methods. According to different brands and budgets, companies can choose the marketing method that can maximize profits.